The Effects of the Two Styles: Concentrated and Distributed Training Workout On The Development Of Some physical and Motor Abilities and Learning the Skill of Spike in Volleyball - Rashid, Thaer; Hussein, Maitham (Journal of Physical Education, 2017)
The study aimed at recognizing the effect of the two styles of work out: the concentrated and the distributed in developing some physical and motor abilities and learning the skill of spike in volleyball. In addition to that, the research aimed at recognizing the best of them in developing some physical and motor abilities and learning the skill of spike in volleyball. The researchers used the experimental method of two equal groups "controlling and experimental" with randomly selected sample and two tests, pretest and posttests. The sample includes (20) players representing the training center of the volleyball branch federation of Diyala province aging from (15-17) during the sport season of 2017. The players were randomly divided into two experimental groups, (10) players for each by a draw. The first group trained using the distributed style while the other (10) players were trained according to the concentrated style. Through the statistical treatments, the researchers found that the best results, represented by the two styles in developing some physical and motor abilities and learning the skill of spike in volleyball. Both training styles were helpful to the coach in learning the skill of spike in volleyball and giving him more chance to notice the players and positively correct their errors. Finally the researchers recommended the necessity of adopting the two styles of training workout: the concentrated and the distributed styles in developing some physical and motor abilities and learning skills in volleyball